Impact of professional qualification on aviation operational safety - Silva, Vanderson da (Revista JRG de Estudos Acadêmicos, 2025)
This literature review critically analyzed the impact of professional qualification on aviation operational safety, considering pilots, cabin crew, maintenance technicians, and organizational programs. The search was carried out in international databases such as PubMed/MEDLINE, Scopus, Web of Science, and IEEE Xplore, in addition to institutional documents from ICAO, IATA, EASA, and FAA, covering publications between 2015 and 2025 as well as relevant classical references. A total of 49 studies and normative documents were included, comprising 28 scientific articles and 21 institutional reports or manuals. The findings showed that contemporary training models such as Competency-Based Training and Assessment (CBTA) and Evidence-Based Training (EBT) are more effective in pilot preparation, while Crew Resource Management (CRM) proved essential for strengthening non-technical skills. Upset Prevention and Recovery Training (UPRT) demonstrated relevance in mitigating Loss of Control-In Flight (LOC-I), and programs focused on human factors, such as MLOSA and MOSS, were effective in aircraft maintenance. At the organizational level, audits such as IOSA were associated with better safety indicators. It is concluded that aviation operational safety depends on the integration of individual qualification, non-technical skills, and organizational safety management systems, although gaps remain in longitudinal and comparative studies capable of robustly measuring the impact of qualification on accident indicators, reinforcing the need for the development of standardized metrics and multicenter analyses to strengthen the empirical evidence base.